The Status and Prospective Study of Tongue Diagnostic in Traditional Chinese Medicine - Chong, Teek Foh; Wong, Kim Tian; Yong, Yii Pin (INTI International University, 2022)
The diagnostic method of Traditional Chinese medicine (TCM) consists of inspection, smelling, listening, inquiry, pulse taking and palpation. Among these, tongue diagnosis from the TCM inspection diagnosis has become one of the most important elements especially during the COVID-19 pandemic period, where TCM physicians diagnose based on tongue inspection through online consultation. This is a preliminary study and objective of this research is to review on the changes of the tongue condition correspondence with the five visceral organs disease and analyse about the tongue diagnosis for enhancing the ability of physicians to differentiate the tongue images effectively. The research data were collected by searching the keywords in China National Knowledge Infrastructure (CNKI) and PubMed from year 2000 to 2021. By choosing the journal articles that analysed tongue diagnosis only in diagnosing the diseases and excluding articles that analysed with the pulse taking or other diagnostic methods. The results showed that different stages of disease are having different manifestation of tongue condition, which reflected with the changes of the pathogenic factor in visceral organs. In conclusion, through the guidance of TCM tongue diagnosis method with the assists of digital technology, it will be performing a huge database to establish a more comprehensive tongue diagnosis theory and unified the diagnostic criteria in a more objective view.